2017
DOI: 10.1016/j.drugalcdep.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Subjective alcohol responses in a cross-sectional, field-based study of adolescents and young adults: Effects of age, drinking level, and dependence/consequences

Abstract: Background Adolescents are physically, cognitively, socially, and emotionally different than adults in ways that may partially explain why alcohol misuse typically develops during this period. Ample animal-science evidence and nascent ecological evidence points toward developmentally limited differences in sensitivity to alcohol’s stimulatory and sedative effects. Field-based research methods were used to test for such age-related differences in a sample of adolescents through young adults. Potential moderatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Targeted BECs between 250 and 350 mg/dL and low to moderate intoxication ratings were chosen to model ethanol consumption patterns in young adults drinkers. Recent reports suggest that in natural environments (i.e., at a bar) adolescent and young adults achieve estimated blood alcohol concentrations within this range ( Treloar et al, 2017 ). Intoxication ratings have been shown previously to correlate with BEC, and indeed our findings revealed that intoxication ratings in both adolescent and adult ethanol exposed animals significantly correlated with BECs ( Figures 2E,F ).…”
Section: Methodsmentioning
confidence: 99%
“…Targeted BECs between 250 and 350 mg/dL and low to moderate intoxication ratings were chosen to model ethanol consumption patterns in young adults drinkers. Recent reports suggest that in natural environments (i.e., at a bar) adolescent and young adults achieve estimated blood alcohol concentrations within this range ( Treloar et al, 2017 ). Intoxication ratings have been shown previously to correlate with BEC, and indeed our findings revealed that intoxication ratings in both adolescent and adult ethanol exposed animals significantly correlated with BECs ( Figures 2E,F ).…”
Section: Methodsmentioning
confidence: 99%
“…A series of studies confirm the additional impact of trigger factors including exposure to stress, biological markers of stress sensitivity, cues, and priming drug doses on key cognitive and behavioral mechanisms associated with alcohol intake [25, 38-40, 41•]. Furthermore, the relative impact of stressors, cues, and priming doses on alcohol intake can differ with age, and indeed, age-related differences in the effects of setting and cues have been reported by first ambulatory assessment studies in substance use disorder [42,43]. Using smartphone-based ecological momentary assessment, a study investigating older adults with and without HIV infection as population showed that greater anxiety predicted subsequent substance use (alcohol and cannabis), greater happiness predicted substance use in the evening and in the night, whereas higher pain levels led to higher consumption in the morning [43].…”
Section: Psychosocial Predictors Of Alcohol Consumption Across the LImentioning
confidence: 99%
“…A fourth approach involves direct ecological assessment of alcohol responses in naturalistic settings. For example, researchers recruited a large sample of participants (ages 17-32 years) from a bar district and collected data on subjective responses [88]. Self-reports of alcoholinduced stimulation were higher in younger compared to older participants, with these differences being more pronounced at lower BACs and among heavier drinkers [88].…”
Section: Examples Of Neurodevelopmental Changes In Alcoholmentioning
confidence: 99%
“…For example, researchers recruited a large sample of participants (ages 17-32 years) from a bar district and collected data on subjective responses [88]. Self-reports of alcoholinduced stimulation were higher in younger compared to older participants, with these differences being more pronounced at lower BACs and among heavier drinkers [88]. Using a similar ecological recruitment approach, researchers found that acute intoxication related to executive functioning deficits in a group of 18-20 year-olds [89].…”
Section: Examples Of Neurodevelopmental Changes In Alcoholmentioning
confidence: 99%